Qualitative and Quantitative Approach to Ordinary Differential Equations through Mathematical Software - Luis_Jaime Collantes_Santisteban; Alberto Hananel; Samuel Collantes; Rosa Gonzales (CLEI Electronic Journal)
The implementation of qualitative and quantitative methods in Ordinary Differential Equations (ODEs) requires the use of mathematical software to achieve a modern approach with effectiveness in geometric and numerical analysis.